Association between hyperglycaemic crisis and long-term major adverse cardiovascular events: a nationwide population-based, propensity score-matched, cohort study. Issue 8 (23rd August 2016) - Chang, Li-Hsin; Lin, Liang-Yu; Tsai, Ming-Tsun; How, Chorng-Kuang; Chiang, Jen-Huai; Hsieh, Vivian Chia-Rong; Hu, Sung-Yuan; Hsieh, Ming-Shun
Abstract : Objective: Hyperglycaemic crisis was associated with significant intrahospital morbidity and mortality. However, the association between hyperglycaemic crisis and long-term cardiovascular outcomes remained unknown. This study aimed to investigate the association between hyperglycaemic crisis and subsequent long-term major adverse cardiovascular events (MACEs). Participants and methods: This population-based cohort study was conducted using data from Taiwan's National Health Insurance Research Database for the period of 1996–2012. A total of 2171 diabetic patients with hyperglycaemic crisis fit the inclusion criteria. Propensity score matching was used to match the baseline characteristics of the study cohort to construct a comparison cohort which comprised 8684 diabetic patients without hyperglycaemic crisis. The risk of long-term MACEs was compared between the two cohorts. Results: Six hundred and seventy-six MACEs occurred in the study cohort and the event rate was higher than that in the comparison cohort (31.1% vs 24.1%, p<0.001). Patients with hyperglycaemic crisis were associated with a higher risk of long-term MACEs even after adjusting for all baseline characteristics and medications (adjusted HR=1.76, 95% CI 1.62 to 1.92, p<0.001). Acute myocardial infarction had the highest adjusted HR (adjusted HR=2.19, 95% CI 1.75 to 2.75, p<0.001) in the four types of MACEs, followed by congestive heart failure (adjusted HR=1.97, 95% CI 1.70 to 2.28, p<0.001). Younger patients with hyperglycaemic crisis had a higher risk of MACEs than older patients (adjusted HR=2.69 for patients aged 20–39 years vs adjusted HR=1.58 for patients aged >65 years). Conclusions: Hyperglycaemic crisis was significantly associated with long-term MACEs, especially in the young population. Further prospective longitudinal study should be conducted for validation.